THE EFFECT OF ACADEMIC PROCRASTINATION ON LEARNING ACHEIVEMENT OF ISLAMIC RELIGIOUS EDUCATION STUDENTS AT SMAN 5 MAKASSAR - M Makbul; Miftahuddin Miftahuddin; Dewi Saputri. S; La Ode Ismail Ahmad (International Journal of Islamic Studies, 2021)
This study aims to (1) determine the level of academic procrastination in students at SMA Negeri 5 Makassar (2) to determine the learning outcomes of students at SMA Negeri 5 Makassar (3) to determine the effect of academic procrastination on student learning outcomes at SMA Negeri 5 Makassar. This type of research uses the expost facto method where academic procrastination is the independent variable and learning outcomes are the dependent variable. The total population in this study was 936 students and the sample taken was 91 students. The research instrument used in this research is a questionnaire (questionnaire) and documentation. The processing and analysis techniques used are descriptive statistical analysis and inferential statistical analysis. Based on the results of processing academic procrastination variables, it can be concluded that academic procrastination has a significant effect on student learning outcomes in Islamic Religious Education and Budi Pekerti lessons. For students at SMA Negeri 5 Makassar in order to improve learning outcomes by reducing the habit of academic procrastination (the habit of procrastinating), and increasing achievement motivation so that they dare to face tasks with full responsibility.